Use of computer based testing of youth hockey players with concussions. - Brooks DA (NeuroRehabilitation, 2007)
Concussion is a potentially serious injury for athletes. Recent statistics suggest that approximately 300 000 sports-related traumatic brain injuries occur annually in the United States. Soccer, rugby, football, and ice hockey are all considered high-risk team sports for concussion. Hockey-related concussions are of particular concern in Canada, where over 500 000 players compete annually in ice hockey. The United States is now registering similar numbers of players. Return to play issues are one of the most difficult issues for physicians caring for concussed athletes. The advent of computerized neuropsychological testing adds another tool to assist in this process. It also appears to enhance the education process for players, coaches, and parents on the potential seriousness of concussion for these young athletes.